2016
DOI: 10.18378/rvads.v11i5.4786
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização físico-química de blend de abacaxi com acerola obtido pelo método de liofilização

Abstract: . As polpas foram homogeneizadas em liquidificador durante 1 min e filtrado em peneira com malha de 2,5 mm, as amostras foram liofilizadas em liofilizador de bancada (Terroni, LS 3000), onde foi desidratada na temperatura de -50 °C por 76 h. A amostra in natura e a liofilizada foram submetidas às analises físico-químicas. Onde foi obtido um teor de água de 92% da amostra in natura e, após o processo de liofilização houve uma redução de 70%. A atividade de água (a w ) foi inferior a 0,30 após a desidratação. Ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Different values of the color parameters were found by Jaeschke et al [ 53 ] when evaluating acerola pulp, obtaining a* = 20.6, b* = 25.0 and L* = 39.9, and in a blend of acerola and pineapple prepared by Silva et al [ 54 ], with results of a* = 35.30, b* = 28.38 and L* = 28.32. This heterogeneity found in relation to the colors depends on several factors, but mainly on the maturation stage, species and variety of the evaluated fruits.…”
Section: Resultsmentioning
confidence: 95%
“…Different values of the color parameters were found by Jaeschke et al [ 53 ] when evaluating acerola pulp, obtaining a* = 20.6, b* = 25.0 and L* = 39.9, and in a blend of acerola and pineapple prepared by Silva et al [ 54 ], with results of a* = 35.30, b* = 28.38 and L* = 28.32. This heterogeneity found in relation to the colors depends on several factors, but mainly on the maturation stage, species and variety of the evaluated fruits.…”
Section: Resultsmentioning
confidence: 95%
“…The samples did not differ significantly, except between BL0 (3.71) and BL10 (3.64), which still had close values. The powdered mixture of acerola and lyophilized pineapple without adjuvants was also classified as highly acidic, with a pH of 3.52 [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…The intensity of yellow (+b*), the predominant hue in BL0, was also progressively reduced with the addition of maltodextrin. In their study of a blend composed of freeze-dried acerola and pineapple, Silva et al [ 19 ] found L* of 42.85 and red (+a*) and yellow (+b*) intensities of 36.39 and 25.75, respectively. In their study characterizing flours obtained from fruit residues, Menezes Filho and Castro [ 31 ] found L* of 58.67, +a* of 12.54 and +b* of 27.60 for the flour obtained from the rind and pulp of ripe guava.…”
Section: Resultsmentioning
confidence: 99%
“…Como esperado, a casca de laranja liofilizada apresentou resultados bastante satisfatórios para remoção de ferro. Observou-se que o processo de liofilização agrega valor a biomassa, pois promove a secagem do material pelo processo de sublimação, mantém as propriedades físico-químicas e a estrutura porosa [73]. Contudo, o alto custo de investimento com equipamentos e o elevado gasto energético ainda são dificuldades operacionais que devem ser levadas em consideração para avaliação de viabilidade de aplicação do biossorvente [38] 3.4 ENSAIO DE BIOSSORÇÃO COM AMOSTRA BRUTA DE ÁGUA DE RIO O ensaio com amostra bruta de água foi realizado com o objetivo de verificar o desempenho da casca de laranja liofilizada na remoção de ferro quando submetida a parâmetros físico-químicos reais de água contaminada pela DAM.…”
Section: Biossorventeunclassified